ULTRASONIC PROPAGATION IN AQUEOUS SOLUTION OF POLYVINYL ACETATE IN VARIOUS CONCENTRATIONS AT DIFFER- ENT TEMPERATURES: Short Communication (Biological Sciences - PJSIR, 2004)
For a polymer solution in the liquid phase, when the high intensity ultrasonic waves are passed over a certain range of temperatures and at atmospheric pressure, the thermodynamic parameters of such polymer can be evaluated by measuring ultrasonic velocity, compressibility and the density (Nozdrev 1974). In binary liquid mixture, the nonlinear variation in ultrasonic velocity with concentration have been frequently observed in many mixtures (Khan 1991; Pandey and Dubey1994).